Maximizing the Role of Micro Waqf Banks as an Alternative Platform for Financial Inclusion in Amboina City - H. Holle, Mohammad; Nur Asiyah, Binti; Saimima, Salma; Muhrim, Muhammad Rifai (AIBPM Publisher, 2024)
The purpose of this study is to maximize the role of Micro Waqf Bank as an alternative financial inclusion platform for micro entrepreneurs in Ambon City. Field research with a qualitative descriptive approach was conducted to describe the phenomenon of micro entrepreneurs who received business capital assistance from Al-Anshor Peduli Ambon Micro Waqf Bank, both in terms of receipt, management and income by collecting data through observation, interviews and documentation. Qualitative analysis using financial inclusion indicators proposed by the Financial Services Authority, namely Access, Use, and Quality. Research shows that from the access indicator, micro entrepreneurs spread across Ambon City are limited by distance, and minimal socialization and information from Al Anshor Peduli Ambon Micro Waqf Bank, an exclusive institution. The usage indicator, it was found that the management of waqf funds by entrepreneurs is decreasing day by day. The use of waqf funds by entrepreneurs is not yet focused. The quality indicator, the use of waqf funds by micro entrepreneurs has not shown any changes in terms of products sold or income levels. The waqf funds used are simply to survive